NBIS-AF2-standard and NBIS-AF2-multimer: CASP15 baseline predictions, Multiple Sequence Alignments and ancillary outputs - Mirabello, Claudio; Elofsson, Arne (Linköping University, 2023)
This dataset contains all AlphaFold (v2.2) monomeric and multimeric predictions used as baseline during CASP15, as well as the input Multiple Sequence Alignments (MSAs) and binary outputs such as distograms etc.

Computations for the CASP15 baseline predictions and MSAs were performed at NSC BerzeLiUs and Tetralith provided by the  Swedish National Infrastructure for Computing (SNIC), partially funded  by the Swedish Research Council through grant agreement no. 2018-05973.

The Snakemake workflow used to generate the models is open source and available at: https://github.com/clami66/AF_server/

Documentation for better reproducibility: http://bioinfo.ifm.liu.se/casp15/reproduce/
Keywords: Bioinformatics and computational biology not elsewhere classified; Structural biology (incl. macromolecular modelling); Medical and Health Sciences; Medicin och hälsovetenskap; Structural Biology; Strukturbiologi; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)